Plantar pressure distribution during gait cycle after subtalar arthroereisis in adolescent flexible flatfoot - Xiong, Nu; Chen, Li; Ru, TianHong; Zhang, Chao; Huang, JiaZhang; Wang, Xu; Ma, Xin (Frontiers in Pediatrics, 2025)
BackgroundFlexible flatfoot is a common foot deformity in adolescents. Subtalar arthroereisis can help reduce excessive foot pronation by placing an implant in the subtalar joint. In recent years, this method has been widely used to treat adolescent flexible flat feet. However, some postoperative complications may occur 3–6 months after subtalar arthroereisis, and few studies have explored plantar pressure and lower limb muscle activation patterns during this period.MethodsTwenty adolescents with flexible flatfoot deformities who underwent subtalar arthroereisis were enrolled in this study. The plantar areas of all patients were divided into eight regions, and the average standing pressure and peak pressure during the gait cycle were compared before and three months after surgery. Surface electromyography (sEMG) of the tibialis anterior (TA), peroneus longus (PL), and medial gastrocnemius (MG) muscles was simultaneously measured during a single gait cycle.ResultsAll patients were able to walk in their shoes at 3 months postoperatively. After surgery, while standing, the average pressure on the lesser toes, lateral forefoot, and lateral midfoot increased significantly (p < 0.05). In contrast, the pressure of the hallux region, medial forefoot, medial midfoot, medial hindfoot, and lateral hindfoot decreased significantly (p < 0.05). During the gait cycle, the peak pressure in the lesser toes, lateral forefoot, lateral midfoot, and lateral hindfoot increased significantly (p < 0.05), whereas that in the hallux, medial forefoot, medial midfoot, and medial hindfoot decreased significantly (p < 0.05). The maximum lateral displacement of the center of pressure (COP) decreased from 3.81 ± 0.56 cm preoperatively to 3.59 ± 0.41 cm postoperatively. The maximum longitudinal displacement decreased from 21.07 ± 3.96 cm to 19.37 ± 3.08 cm (p < 0.05), and the COP trajectory curve shifted laterally. During the gait cycle, the peak activation percentage of TA significantly decreased postoperatively, that of the PL significantly increased after surgery, and that of the MG significantly decreased. The integral percentage of TA activation was significantly reduced postoperatively. The integral percentage of PL activation was significantly higher than that at the preoperative stage. Additionally, the integral percentage of MG activation was significantly lower than that of the preoperative value. (all p < 0.05).ConclusionThis study found that plantar pressure shifted laterally during the early postoperative period. Such changes in plantar pressure distribution may compensate for alterations in lower limb muscle activation patterns, which may potentially contribute to postoperative plantar pain or painful peroneal muscle spasm. Therefore, monitoring plantar pressure distribution and muscle activation in the early postoperative period is recommended.